Influence of stirring process during slurry formation on the casting defects and high-temperature fatigue of rheocast AlSi7Mg alloys. Issue 1 (1st January 2023) - Zaffarani, P; Zhang, Q; Jarfors, A E W; Timelli, G
Abstract: The effects of the stirring phase during slurry formation on the defect's content and the influence on the high-temperature fatigue behaviour of a rheocast AlSi7Mg alloy were investigated. Single or double-stir step was used during RheoMetal processing. Metallographic and image analysis techniques were performed to quantitatively examine the defect's changes occurring with different stirring methods. Samples were cross-sectioned along the gauge length, and the pores content was measured. Uniaxial fatigue tests were performed at high temperature (150 °C) with the staircase method, applying a stress ratio of R = −1. Fracture surfaces were examined using a scanning electron microscope to determine the fatigue crack initiation sites, type and size of the defects. Shrinkage porosity has more probability of acting as a crack initiator than gas porosity or oxides. The double-stir step effectively reduces the size of pores compared to the conventional technique; it reduces porosity to less than half if compared to the single-stir process. Shrinkage pores distribution show a higher population of smaller pores for the double-stir process. According to the Dixon-Mood formula, the mean fatigue strengths are comparable. The capability of the double-stir to reduce porosity is evident, even having no significant effect on the high-temperature fatigue life.